2019
DOI: 10.1029/2018jd029205
|View full text |Cite
|
Sign up to set email alerts
|

Antarctic Ice Cloud Identification and Properties Using Downwelling Spectral Radiance From 100 to 1,400 cm−1

Abstract: One year (2013) of high spectral resolution measurements of downwelling radiance in the 100–1,400 cm−1 range, taken by the Fourier Transform Spectrometer REFIR‐PAD at the research station Concordia (Antarctic Plateau), is analyzed. Optically thin ice clouds are identified by means of a new identification/classification tool based on a Support Vector Machine algorithm. The use of transparent microwindow channels in the Far InfraRed (FIR) spectral region (100–667 cm−1) is shown to be of great importance in the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…Moreover, in Palchetti et al (2016) it is shown that by using the full infrared emission spectrum more information may be retrieved about cirrus cloud microphysical properties. In Maestri et al (2019), it is shown that the Radiation Explorer in the "Far InfraRed: Prototype for Applications and Development" (REFIR-PAD) channels hold additional information for cloud detection and cloudphase classification from ground-based measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in Palchetti et al (2016) it is shown that by using the full infrared emission spectrum more information may be retrieved about cirrus cloud microphysical properties. In Maestri et al (2019), it is shown that the Radiation Explorer in the "Far InfraRed: Prototype for Applications and Development" (REFIR-PAD) channels hold additional information for cloud detection and cloudphase classification from ground-based measurements.…”
Section: Introductionmentioning
confidence: 99%
“…OD =0.5 and OD= 5). This suggests that the analysis of combined observations in the FIR and MIR part of the spectrum, acquired with a brightness temperature accuracy of 0.1 K as required for the FSI measurements, might be sufficient to allow an identification of the crystal habits, as recently shown Maestri et al (2019a).…”
mentioning
confidence: 83%
“…Despite this, their role for cloud feedback is not yet completely understood [9]. Recently, simulations have been used to show that FIR can contribute to improve the detection of thin cirrus cloud [4,10] and that FIR and MIR measurements can be combined to efficiently retrieve the cloud properties and the atmospheric state (water vapor and temperature profiles) [11,12]. The detection of thin cirrus clouds and the derivation of some of their features have been improved by using active satellite sensors [13][14][15].…”
Section: Introductionmentioning
confidence: 99%